Pemphigus foliaceus patients (Fogo Selvagem) treated with kinesiotherapy presented lower levels of proinflammatory cytokines - Timóteo, Rodolfo Pessato (J Exerc Rehabil, 2019)
Fogo Selvagem (FS) is a rare autoimmune disease characterized by acantholysis and inflammation of the epidermis. It was evidenced in this disease the increase of proinflammatory cytokines levels which can be influenced by physical activities. Kinesiotherapy, as physiotherapeutic interventions, was associated improvement levels of the quality of live, mainly the pain. Understanding the impact of such methodology in immunology of the FS, may constitute an alternative and effective approach. We compare the levels of serum cytokines and chemokines between nine patients with FS submitted to kinesiotherapy for 12 weeks and ten patients not submitted to kinesiotherapy. The kinesiotherapy was composed by self-stretching followed by a resistance training for upper and lower limbs. The protocol was carried out in three sections of eight to ten repetitions with 70% of the maximum load measured by test maximum of ten repetitions. After strengthening period patients performed a passive stretching. The training sessions lasted 50 min and were performed 3 times a week at least 12 weeks. Cytokines and chemokines were assessed in plasma using enzyme-linked immunosorbent assay and/or cytometric bead array. Patients with FS were being kinesiotherapy presented minors levels of interferon-γ, interleukin (IL)-17, IL-22, and IL-15 when compared to those not submitted to kinesiotherapy. No differences were observed for the detection of the chemokines chemokine ligand (CCL)-2, CCL-3, CCL-5, CCL-11, C-X-C motif chemokine 8 (CXCL-8), and CXCL-10. These results suggest that kinesiotherapy had a positive impact on inflammatory markers that are associated with disease worsening in FS.